Technology Transfer as a Function of Position in the Spectrum from Research Through Development to Technical Services - Allen, Thomas J.; Tushman, Michael L.; Lee, Denis M. S. (Academy of Management Journal, 1979)
The manner in which research and development projects most effectively acquire new technology is shown to vary with the nature of the project. Research projects perform best when all project members maintain high levels of communication with colleagues outside their organization. Product and process development projects, on the other hand, show higher performance when external communications are monopolized by one or a few project members.